Scientific Collaboration and Sustainable Development: A Bibliometric Analysis of the Andean Region, Panama, and Spain - Gresky Gutiérrez-Sánchez; Patricio Álvarez-Muñoz; Purificación Galindo-Villardón; Purificación Vicente-Galindo (Publications)
Background: Scientific collaboration has become a cornerstone of sustainable development, particularly in regions where research capacity and funding face significant challenges. The Andean region, Panama, and Spain offer a unique perspective due to their cultural and linguistic ties, alongside varying levels of scientific production and innovation. These disparities present opportunities for collaboration and targeted interventions to foster regional growth and contribute to global priorities. According to UNESCO, Latin America invests merely 0.56% of its GDP in research and development, underscoring the pressing need for innovative strategies to enhance scientific capacity and align efforts with the United Nations Sustainable Development Goals (SDGs). Methods: This study employed HJ-Biplot and MANOVA-Biplot methodologies to analyze bibliometric data across various thematic areas. These multivariate techniques offer a comprehensive exploration of the interrelationships between scientific production, research talent, and international collaboration, revealing significant patterns and associations. The data were sourced from the Scimago Iberoamerican platform, which aggregates information from Elsevier’s Scopus database on scientific journals and countries. The platform provides data in five-year increments, capturing trends in scientific output, international collaboration, and thematic focus across the Andean region, Panama, and Spain, spanning the period from 2012 to 2022. Results: The analysis identified significant correlations between scientific productivity, research talent, and international partnerships. Clustering disciplines such as engineering, computer science, and energy highlights the strong intersections between technology and economic development. The proximity of psychology and environmental sciences emphasizes the importance of social and environmental factors in scientific research. Conclusion: This study provides a comprehensive bibliometric analysis of the Andean region, Panama, and Spain, identifying critical drivers of scientific productivity and collaboration. The integration of advanced statistical methodologies reveals key associations between research talent, international partnerships, and thematic focus areas. While areas such as environmental sciences and biochemistry demonstrate alignment with innovation and sustainability goals, disciplines like engineering and mathematics require targeted investment to enhance their contributions. These findings underscore the importance of a balanced approach to research funding and policymaking to ensure equitable and impactful scientific development across regions. The results serve as a roadmap for fostering collaboration, strengthening leadership, and aligning research efforts with sustainable development objectives globally.